Sexuality and Attachment in Clinical Practice. - Schwartz, Joseph (Karnac Books, 2005)
The second book in the John Bowlby Memorial Conference Lecture Series. It explores our thinking about the developmental, relational and interpersonal aspects of the links between attachment and sexuality as they emerge in clinical practice.